2016
DOI: 10.1002/dneu.22463
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and crosstalk in axon guidance cue integration: Additivity, synergy, and fine‐tuning in combinatorial signaling

Abstract: Neural circuit development involves the coordinated growth and guidance of axons to their targets. Following the identification of many guidance cue molecules, recent experiments have focused on the interactions of their signaling cascades, which can be generally classified as additive or non-additive depending on the signal convergence point. While additive (parallel) signaling suggests limited molecular interaction between the pathways, non-additive signaling involves crosstalk between pathways and includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 112 publications
(162 reference statements)
0
29
0
Order By: Relevance
“…Several lines of evidence have shown that Netrin and Slit signals can interact in diverse ways in the different nervous systems, including Slits acting through a co-receptor complex to switch on Netrin attraction for thalamocortical axons, and the opposite effect of Netrin attenuation of Slit repulsion (Bielle et al, 2011; Fothergill et al, 2014; Leyva-Díaz et al, 2014; Morales and Kania, 2016). In addition, the parallel independent Netrin and Slit guidance of fly commissural axons has been reported (Garbe and Bashaw, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have shown that Netrin and Slit signals can interact in diverse ways in the different nervous systems, including Slits acting through a co-receptor complex to switch on Netrin attraction for thalamocortical axons, and the opposite effect of Netrin attenuation of Slit repulsion (Bielle et al, 2011; Fothergill et al, 2014; Leyva-Díaz et al, 2014; Morales and Kania, 2016). In addition, the parallel independent Netrin and Slit guidance of fly commissural axons has been reported (Garbe and Bashaw, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All of these cues can—and do—impinge on commissural growth cones simultaneously, not necessarily producing simple additive effects (Butler & Dodd, ; Sloan et al, ). The study of how multiple molecular cascades are integrated to produce a coherent cellular response is an area rich in investigation (reviewed in Dudanova & Klein, ; and in Morales & Kania, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, combinatorial signaling, or the integration of multiple pathways, is another well-established means to increase the information available to cells from limited numbers of signaling pathways. Combinatorial signaling is used repeatedly in metazoan development, from cell-fate specification to axon guidance (Briscoe and Small, 2015; Cornell and Kimelman, 1994; Flores et al, 2000; Morales and Kania, 2016). …”
Section: Patterningmentioning
confidence: 99%